Does Risk Preferences Executive Influence the Relationship betwen Corporate Social Responsibility Disclosure and Tax Avoidance? - Wisnu Dewi Fitriyani; Vita Elisa Fitriana, S.E., M.Sc. (JAAF (Journal of Applied Accounting and Finance), 2020)
This research aims to examine the influence of the corporate social responsibility (CSR) disclosure towards the tax avoidance by considering corporate governance which is risk preferences executive. The sample that used in this study are 55 manufacturing companies listed in Indonesia Stock Exchange period 2014-2017. The researcher used regression analysis for analyzing the data. The result shows that corporate social responsibility disclosure using the proxy of Global Reporting Initiative G4.0 significantly influences tax avoidance. Risk preferences executive as the indipendent variable and moderating variable between corporate social responsibility disclousre and tax avoidance both has significant influence. The risk preferences executive as moderating variable in this study reveals a positive significant influence that proves the risk preferences executive strengthen the relationship between corporate social responsibility disclosure and tax avoidance.